Consumer Demand and Satisfaction Preferences Regarding Organic Coffee Products - Lestari, Astria Rani; Noer, Irmayani; Analianasari, Analianasari; Fitriani, Fitriani (AIBPM Publisher, 2025)
Coffee is one of Indonesia’s top plantation export commodities and plays a vital role in the national economy. Organic coffee is growing steadily due to its added value, particularly its high antioxidant content and unique flavor. With increasing domestic coffee consumption, demand for organic coffee is also rising. Consumer preferences represent their desires and expectations for a product and help guide marketing strategies. This study analyzes consumer preferences and satisfaction toward organic coffee using conjoint analysis. The findings show that most organic coffee consumers are women (60%), aged 19–32 years (89.6%), unmarried (81.2%), hold a diploma or bachelor’s degree (64%), work in the private sector (26.8%), and earn between Rp1,000,000–3,000,000 (43.6%) or more than Rp3,000,000 (34.8%). Consumers choose organic coffee based on personal preference, especially cappuccino or latte flavors, and make purchases as needed without external influence. Consumers are generally satisfied, prioritizing taste and quality. Despite price increases, they remain loyal due to quality, flavor, and health benefits. Preferred attributes include a slightly sweet taste, smooth texture, dark brown color, strong aroma, affordable price, and easy availability.